2001
DOI: 10.1523/jneurosci.21-24-j0001.2001
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Enhances NMDA Receptor Function and Modulates Hippocampal Synaptic Plasticity

Abstract: The obese gene product leptin is an important signaling protein that regulates food intake and body weight via activation of the hypothalamic leptin receptor (Ob-Rb; Jacob et al., 1997). However, there is growing evidence that Ob-Rb is also expressed in CNS regions, not directly associated with energy homeostasis (Mercer et al., 1996; Hakansson et al., 1998). In the hippocampus, an area of the brain involved in learning and memory, we have found that leptin facilitates the induction of synaptic plasticity. Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
391
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(410 citation statements)
references
References 44 publications
14
391
3
2
Order By: Relevance
“…Moreover, direct administration of leptin into the dentate gyrus enhances LTP in rats (Wayner et al, 2004), while direct leptin administration into the CA1 region of the hippocampus improves spatial memory and learning in mice (Farr et al, 2006). At the cellular level, leptin has been shown to enhance NMDA receptor function (Shanley et al, 2001), possibly through rapid trafficking of NMDA receptors to the plasma membrane (Harvey et al, 2006), in a manner analogous to insulin (Skeberdis et al, 2001). Thus leptin may enhance memory and learning through mechanisms that modulate synaptic plasticity in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, direct administration of leptin into the dentate gyrus enhances LTP in rats (Wayner et al, 2004), while direct leptin administration into the CA1 region of the hippocampus improves spatial memory and learning in mice (Farr et al, 2006). At the cellular level, leptin has been shown to enhance NMDA receptor function (Shanley et al, 2001), possibly through rapid trafficking of NMDA receptors to the plasma membrane (Harvey et al, 2006), in a manner analogous to insulin (Skeberdis et al, 2001). Thus leptin may enhance memory and learning through mechanisms that modulate synaptic plasticity in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, leptin facilitates learning, spatial memory and long term potentiation (Li et al, 2002), and has been shown to enhance NMDA receptor function and modulate synaptic plasticity in the hippocampus (Shanley et al, 2001). Recent work by Fewlass et al (2004) reveals that leptin may be linked to Alzheimer's disease (AD) through modulation of Aβ production and clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin may affect Aβ degradation via an insulin‐degrading metalloprotease. It has been observed that the decreased activity, low concentrations, and small amounts of mRNA of insulin‐degrading enzyme in brains of patients with AD and knockout mice that lack the enzyme have reduced degradation of Aβ and insulin in brain (Lam & Lu, 2007; Li et al, 2002; Shanley, Irving, & Harvey, 2001). Similarly, insulin resistance is commonly observed in older adults (Barzilai, Huffman, Muzumdar, & Bartke, 2012; Morley, 2008).…”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%
“…In accordance with the high levels of leptin receptor expression detected at hippocampal synapses [6], evidence is growing that leptin is a potent modulator of hippocampal excitatory synaptic function [11][12][13][14][15]. Indeed, studies in obese leptin-insensitive rodents (Zucker fa/fa rats; db/db mice) have identified deficits in hippocampal long-term potentiation (LTP) and long-term depression (LTD) as well as spatial memory [16,17].…”
Section: Introductionmentioning
confidence: 96%